LINGUISTIC AND CULTURAL ASPECTS OF CHILDREN’S ANECDOTES IN ENGLISH AND UZBEK LANGUAGES - Bahriddinova , Mohinabonu (Educational Research in Universal Sciences, 2024)
Anecdotes, as a form of storytelling, offer a unique insight into the language and culture of a particular community. This study aims to analyze the linguistic features and cultural themes present in children’s anecdotes in both English and Uzbek languages. It highlights the importance of understanding the intersection of language and culture in children’s storytelling and its implications for language learning and teaching.